Teaching in a Digital Age : Guidelines for Designing Teaching and Learning - Bates, A. W. (Tony) (BCcampus, 2015)
The book examines the underlying principles that guide effective teaching in an age when everyone, and in particular the students we are teaching, are using technology. A framework for making decisions about your teaching is provided, while understanding that every subject is different, and every instructor has something unique and special to bring to their teaching. The book enables teachers and instructors to help students develop the knowledge and skills they will need in a digital age: not so much the IT skills, but the thinking and attitudes to learning that will bring them success.
Accepted: 2018-02-26T20:55:21Z